Re-evaluating the Form and Communication of Social Robots: The Benefits of Collaborating with Machinelike Robots - Sandry, Eleanor (2015)
This paper re-evaluates what constitutes a social robot by analysing how a range of different forms of robot are interpreted as socially aware and communicative. Its argument juxtaposes a critical assessment of the development of humanlike and animal-like robotic companions with a consideration of human relations with machinelike robots in working teams. The paper employs a range of communication theories alongside ideas relating to anthropomorphism and zoomorphism in discussing human–robot interactions. Some traditions of communication theory offer perspectives that support the development of humanlike and animal-like social robots. However, these perspectives have been critiqued within communications scholarship as unethically closed to the possibilities of otherness and difference. This paper therefore reconfigures and extends the use of communication theory to explore how machinelike robots are interpreted by humans as social and communicative others. This involves an analysis of human relations with explosive ordnance disposal robots and with the robotic desk lamp, AUR. The paper positions social robotics research as important in understanding working teams containing humans and robots. In particular, this paper introduces the value of tempered anthropomorphism and zoomorphism as processes that support communication between humans and machinelike robots, while also ensuring that a sense of the otherness of the machine and respect for its non-human abilities is retained.